Multilingual dictionary of keywords as a tool for the digital bibliographic database of world Slavic linguistics - Kowalski, Paweł (Array, 2020)
The paper presents the structure of a multilingual dictionary of keywords, which is an integral part of the bibliographic database of Slavic linguistics iSybislaw representing the digital information retrieval system (www.isybislaw.ispan.waw.pl). The lexical units (keywords) of the language of keywords used in the system are represented primarily by linguistic terms. In spite of a different denotation – the keywords directly denote sets of documents, and indirectly the non-documentary reality, while the terms denote elements of linguistic reality – they are formally equal with linguistic terms, which allows them to map the semantic field of a particular discipline, in this case Slavic linguistics. The dictionary is therefore a domain-based online specialist dictionary, which is a tool for users of the bibliographic database of Slavic linguistics. The dictionary is addressed to all those who deal with linguistics and linguistic terminology, first of all to scholar-linguists, Ph.D. students and students of philologies, as well as translators of academic papers in the field of linguistics.